Pequenas crianças, grandes leitoras: práticas de leitura literária na Educação Infantil - Zerbini, Silvia Nogueira (2023)
The problem of the present research originated from a perception built throughout many years working as a young children´s teacher and sharpened after the enrollment in the Literature for children specialization course, offered by the Instituto Superior Vera Cruz, in São Paulo, Brazil. This perception concerns the place that literary reading occupies in the early childhood school's routine. Often, it occurs in the gaps between one activity and the other - in order to fill leisure time or to calm down the kids -, or to complement a project held by the group. On the few times that it has a purpose in itself, generally, it's not a planned and documented experience or becomes a subject of thought. Added to this perception is the matter of the teachers' professional development, that rarely includes children's literature and reading practices. Therefore, the main goal of this work is to analyze the current reading practices in the early childhood schools, emphasizing the teacher's role, and, from the produced data, write a formative itinerary. In order to pursue this goal, observation was held inside six classrooms of a school in São Paulo and a questionnaire was applied to its teachers. The information created by these two data collection strategies was summarized and organized into the following categories: What concerns readers development in early childhood, The importance of having someone to share the reading experience with, Literature as an experience, Reading contexts inside the school, Reading mediation / Literary talk and Other observations. This information was, then, analyzed in the light of the theories of the following specialists: Yolanda Reyes, Evelio Cabrejo Parra, Maria Emilia Lopez, Cecilia Bajour, Graciela Montes, among others. This analysis showed that, even though the teachers are aware of the importance of reading to young children, they are not sure how to plan, organize or experience reading contexts with their students. The formative itinerary suggested in the present work was written based on this outcome and intended to invite teachers to relate to literature as an experience, giving up conceptions that make it a senseless curricular obligation